The potential of bicycle commuting to reduce carbon emissions in Finland - Emilia Suomalainen; Marko Tainio (PLoS ONE, 2025)
There is an increasing amount of evidence that cycling is an effective way to decarbonise everyday mobility. The potential of cycling is however less well understood in cold climates, where seasonal weather conditions are seen as a major obstacle. This work explores the potential of cycling to substitute for car use on commute trips in Finland. A binary logistic regression model is first built based on national travel survey data to describe cycling behaviour on home–work trips according to trip distance, hilliness, temperature, snow cover, gender of the cyclist, car availability, and city region. This model is then used to quantify cycling uptake scenarios and estimate cycled mileage, replaced car travel, and climate emission reductions. E-bike scenarios are also explored. The results indicate that it would be possible to set ambitious targets for cycling uptake, even doubling the mileage cycled, leading to non-negligible emission reductions.